First record of Grey-streaked Flycatcher in Kalimantan - Bas van Balen; Simon Aspinall (KUKILA, 1996)
On 15 February 1992, while surveying the bird fauna of the Kayan Mentarang proposed national park in East Kalimantan, BvB observed two single, small flycatchers in the primary forest on a ridge above the Anye' Bung rivulet, north of the Lurah river, which is a branch of the Bahau river (at 2°42' N, 115°46' E) north of Peliran. The first bird was observed at 1050m a.s.1. at 10.03 hrs, the second at 12.12 hrs at 1200m in a forest gap on the same ridge.